Seeing, surfacing, patterning: A socially inclusive architecture for the blind - De Bok, Saskia (School of Architecture, Planning and Geomatics, 2024)
Architectural design possesses the dual capacity to either inflict or transverse spatial barriers in our built environments, which prevent people from accessing and interacting with the built environment, and in turn imparts consequences on the social order of our cities. This dissertation inquires into the manners in which the spatial configurations of our cities often adversely affect the social mobility of blind and visually impaired communities, leading to their exclusion from public social practices. Instead, this dissertation intends to uncover architectural design strategies that would contribute to the social integration of persons with sight impairments in correspondence with the prominent Western Cape non-profit organisation The League of Friends of the Blind. Further, the concern is not merely with how buildings could be designed to better accommodate this community, but also shifts focus to how the ‘urban surface' (Wall, 1999) within which these buildings are situated could do the same; extending the concept of enabling design beyond the confines of interior spaces into the public urban network.